Leading Islamic University Through Excellent Higher Pesantren: Challenges, and Strategies in Integrated Curriculum Development - Thoyib, Muhammad; Nurdin, Muhammad; Djohan, M Widda (Program Studi Pendidikan Agama Islam, 2020)
Along with the pace of globalization, and the severity of educational competitions, not a few actors of Islamic higher education tried to integrate two 'educational entities' (university and pesantren), in an integrated education curriculum system. Some were successful, but not a few was failed. This qualitative research article is based on interactive model data analysis technique that aims to 'initiate' the efforts of integrated curriculum development model of excellent higher pesantren at UII Yogyakarta, considering its good institutional achievement, so it should be the pilot project of the integration effort. This research concluded that the indigenous values in integrated curriculum development based on its excellent pesantren are to be oriented at the value of establishment of a 'progressive-inclusive-integrative' scholars candidate. The challenges of its integrated curriculum development include the alignment of synergical idea of university values and modern pesantren; institutionalization of university and pesantren policies; and integrating the curriculum products of university-based pesantren and community service. While, the strategies of its integrated curriculum development are implementing a top down and bottom up approach that involve all its stakehoders through a forum for feasibility of pesantren curriculum development that supported by phases that are determination of the pesantren curriculum enforcement area, development procedures; curriculum implementation; and evaluation results. However, it still needs strengthening ‘the outsider’s perspective’, especially from the users of its pesantren curriculum products in order to be able more adaptive to global needs as the idea of Beauchamp